Formulación y determinación de parámetros tecnológicos para la obtención de un alimento infantil a ase de puré de frutas tropicales banana(musa paradisiaca), papaya (carica papaya) y mango (manguifera indica) - Lozano Reategui, Ronald Marlon (1999)
a children's food was developed based on a mix of 1: Jures mango, which was enriched with milk powder rehydrated skimmed, precooked quinoa, raw cassava flour and rice, and as a sweetener refined white sugar. The developed product is intended snack-lunch module and corresponds to dP dessert instantaneous consumption whose characteristics Textural make it easy to assimilate because no You will need greater effort to swallowing and also It has the natural characteristics of the fruits used as raw materials. The baby food is made with 60% the mixture of fruit purees (banana, papaya, mango), in 30% rehydrated skim milk powder, and in a .1.0i ~ c: cin mixtures of flour (cassava, quinoa) more white sugar. six (06) attempts formulas were developed, the which were subjected to a sensory analysis 1 '...) .. semi-trained panelists using the assessment test quality parameters of Karlsruhe, whose results They were analyzed statistically using the DBCA withhours differences found between treatments by Tukey test. As there were two (02) formulas together excellent organoleptic characteristics of color, appearance, ol.cw, flavor and texture, had to use descriptive Quantitative Descriptive Analysis test (Q.D.A.), in order to obtain the optimal formula present study. This test determined that the formula F1-5 (fruits 60%, milk 30%, sugar 10% flour + e = 5 min; T = 85 ° C) to show superiority to the formula Fl- (Fruits 60%, milk 30%, sugar 10% flour + e = 15 min; T 80), will be established as the best formula, the same as produced according to the following flow chart: raw, heavy, formulated materials, mixing, packaging / sealing, heat treatment, cooling, storage, whose parameters shown in Figure 11. The optimal formula was evaluated through analysis physical, chemical and microbiological, subjecting it to a 30 days storage. In addition we studied its acceptability in children aged 6-7 years that is preschool. It was found to provide 100 g product 1.68 g protein, 1.62 g of fat, 20.83 g of carbohydrates, with a caloric value of 104.67 kcal. Both sensory and microbiological quality was Excellent. The product obtained showed the feasibility of to employ a formula based on fruits, milk, flour and sugar to produce a baby food to For dessert, using a simple technology, smaller cost and as an alternative to improve food ni ~ os preschool and school age.